Advanced mathematical model for reservoir heat efficiency with liquid in steam-injection wellbore. Issue 1 (2nd January 2019) - He, Congge; Xu, Anzhu; Fan, Zifei; Zhao, Lun; Cheng, Youyou; Bo, Bing; Luo, Erhui
ABSTRACT: The accurate determination of reservoir heat efficiency of steam injection in heavy oil reservoirs is very important for heating radius calculation and production dynamic prediction. In conventional calculation methods of reservoir heat efficiency, the steam-injection wellbore is assumed as taking steam over the entire height. In fact, a liquid level in steam-injection wellbore is a very significant observation with respect to the steam override. Aiming at the actual situation that the steam-injection wellbore always has a liquid level, combined with the formation temperature distribution, the new mathematical model for reservoir heat efficiency with the consideration of liquid in steam-injection wellbore was established based on the Van Lookeren steam override theory and the energy conservation principle. The established mathematical model was used to calculate and analyze the reservoir heat efficiency of steam injection in heavy oil reservoirs. The results show that because the new mathematical model considers the liquid in the steam-injection wellbore, the predicted results are more reasonable, thus verifying the correctness of the new model. According to the influential factors analysis based on the new model, it is observed that although increasing the steam quality can effectively increase the steam-taking degree of the steam-injection wellbore, it has limited impact on reservoir heat efficiency. Moreover, the larger the steam-injection rate, the higher the steam-taking degree and reservoir heat efficiency. The reservoir heat efficiency decreases with the pay-zone thickness when the steam-injection wellbore has liquid.